Innovative combined topical remedy in the treatment of complicated dermatoses: experience of the application - N. V. Kungurov; M. M. Kokhan; Yu. V. Keniksfest; Ya. V. Kascheeva; O. V. Letaeva; I. A. Kuklin; E. I. Stukova (Лечащий Врач, 2021)
Generalization of clinical experience of the treatment of 56 patients with chronic dermatoses (atopic dermatitis, eczema, bullous dermatoses) including with secondary pyoderma was used. In the treatment of this patients, we used a new combined drug, containing topical glucocorticosteroid in combination with an antibiotic, antifungal agent and a component that promotes skin repair. Dynamic clinical observations of patients showed that the use of the new drug, both in monotherapy mode, and in the complex treatment of patients, conducted in outpatient and hospital modes, contributed to regression of pyogenic complications and the achievement of clinical remission of the main skin process, the restoration of the quality of life in the vast number of patients, without the formation of side effects and complications from therapy.